If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -5)(2x + 5) = equation Reorder the terms: (-5 + 2x)(2x + 5) = equation Reorder the terms: (-5 + 2x)(5 + 2x) = equation Multiply (-5 + 2x) * (5 + 2x) (-5(5 + 2x) + 2x * (5 + 2x)) = equation ((5 * -5 + 2x * -5) + 2x * (5 + 2x)) = equation ((-25 + -10x) + 2x * (5 + 2x)) = equation (-25 + -10x + (5 * 2x + 2x * 2x)) = equation (-25 + -10x + (10x + 4x2)) = equation Combine like terms: -10x + 10x = 0 (-25 + 0 + 4x2) = equation (-25 + 4x2) = equation Solving -25 + 4x2 = aeinoqtu Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 4x2 = 25 + aeinoqtu Combine like terms: -25 + 25 = 0 0 + 4x2 = 25 + aeinoqtu 4x2 = 25 + aeinoqtu Divide each side by '4'. x2 = 6.25 + 0.25aeinoqtu Simplifying x2 = 6.25 + 0.25aeinoqtu Reorder the terms: -6.25 + -0.25aeinoqtu + x2 = 6.25 + 0.25aeinoqtu + -6.25 + -0.25aeinoqtu Reorder the terms: -6.25 + -0.25aeinoqtu + x2 = 6.25 + -6.25 + 0.25aeinoqtu + -0.25aeinoqtu Combine like terms: 6.25 + -6.25 = 0.00 -6.25 + -0.25aeinoqtu + x2 = 0.00 + 0.25aeinoqtu + -0.25aeinoqtu -6.25 + -0.25aeinoqtu + x2 = 0.25aeinoqtu + -0.25aeinoqtu Combine like terms: 0.25aeinoqtu + -0.25aeinoqtu = 0.00 -6.25 + -0.25aeinoqtu + x2 = 0.00 The solution to this equation could not be determined.
| 45xy-72zw= | | 9m^2-4/49 | | (2x^2-3x)(3x^2+2x-1)=equation | | (x+7)(3x-2)=equation | | Y=-0.4x(x-14) | | 6/x-2=-5 | | (4x^2+7x)(5x^2-3x)=equation | | 7m^2+45mn-28n^2=0 | | 2(9/8-x/10)+x/3=5 | | x^2+16-17=0 | | X-10x+25=45 | | .06+(.10-.06)1.2= | | (4x^2-3x)(5x^2-6x+2)=equation | | x=2v+at^2 | | (5x^2+2x)(3x^2-7x+4)=equation | | x^4+4x^3-15x^2-18=0 | | 1/10*31/10 | | (4x-5)(4x+5)=equation | | 4+2m-2=9m+34-3m | | (-4.9)(7.2)= | | 1.2p-3.6=0.6p-6.4-2.6p | | (x^2-5x)(2x^2+x-3)=equation | | (1/4)+(2/x)=(11/4x) | | 1/3c-(-5)=11 | | y^2-14y=-26 | | y+10=-4 | | 3+n/4=-11 | | 5x-6=2(3x-1)-x | | 2x=(x+11)2 | | -5x-4(x-6)=12 | | (x)+3=5 | | (2x^2-4x)(6x^2-5x)=equation |